Estudo da influência da radiação ionizante na tração diametral de cimentos de ionômero de vidro - Carvalho, Lígia Maria Nogarett Pibernat de (2013)
The aim of this study was evaluate the influence of ionizing radiation under three glass ionomer (conventional, resin modified and silver added) on the diametral tensile strength. The null hypothesis tested the action of ionizing radiation under glass ionomer cements submitted to tensile strength. To diametral tensile strength, samples were made with conventional (n=20), resin modified (n=20), silver added glass ionomer cements (n=20) into a cylindrical bipartite mould of PTFE (polytetrafluoroethylene) with 6 mm diameter X 3 mm high according to manufacturer s instructions. All samples were stored in plastic tubes protected from light for 24 h at 37° C in a culture stove. After that, each group was divided in a control or submitted to ionizing radiation at Centro de Oncologia do Hospital Mãe de Deus, with usual dose for head and neck cancer fractioned in 35 daily applications of 2 Gy (200cGy) for each Day, resulting at 70 Gy (7000cGy) by a linear accelerator. In order to avoid sub dosage at the material surface due to Build-up effect, a Bolus was used with 2mm simulating soft tissues. The diametral tensile strength test was performed in a universal testing machine EMIC DL 2000 (Emic, São José dos Pinhais, Brazil), with 1 mm/min of cross-head speed. Data were submitted to analysis of variance and multiple comparison test of Tukey (α=0.05). Significant differences were recorded (p<0.001) between the glass ionomer tested (conventional, resin modified and silver added) for diametral tensile strength. Comparing groups with the same classification, submitted or not to radiation, there was no significant difference. Riva Light Cure control showed an average (MPa) of 31.83 in comparison to 24.82 of irradiated group. Riva Silver control showed an average (MPa) of 12.06 in comparison to 17.29 for the irradiated group. Riva Self Cure control showed an average (MPa) of 14.05 in comparison to 26.04 irradiated group. Comparing all groups of different classification submitted to ionizing radiation, there were significant difference between them (p<0.001). Riva Silver control showed the lowest average (MPa) (12.03) in comparison to Riva Light control (31.83). The radiotherapy applied as protocol to head and neck cancer therapy do not act negatively in the diametral tensile strength of the three glass ionomer tested.